Science and Technology Study Tools for Education on Digitality and Digital Technologies - Samaniego, José Miguel (2023)
This essay offers several tools from various science and technology studies (STS) branches, for the education on and with digital technologies and digitality. Emblematic STS works that have researched the digital are first discussed, followed by a brief review of the main theories and concepts that have been applied for this purpose. The paper is then concluded with a synthesis of relevant STS understandings to study the digital, in addition to a set of teaching elements for its education and some applicable lessons for a critical pedagogy on this issue.